Structural design and optimization of metal-organic framework-derived FeOx@C/rGO anode materials for constructing high-performance hybrid supercapacitors. (1st May 2022) - Sun, Lei; Cai, Yingying; Haider, Md. Kaiser; Miyagi, Daisuke; Zhu, Chunhong; Kim, Ick Soo
Abstract: Hybrid supercapacitors are promising energy storage devices that bridge the performance gap between conventional capacitors and batteries. However, the backward development of anode materials is a key issue that hinders the performance improvement of the hybrid supercapacitors. Therefore, this study proposes a strategy to fabricate reliable FeO x -based (Fe2 O3 or Fe3 O4 ) anode materials using the Fe-based metal-organic framework (Fe- MOF) as a template. Polyvinyl pyrrolidone (PVP) was used to stabilize and regulate the morphology of the Fe- MOF template to ensure a desirable microstructure of the final product. A series of FeO x @Carbon nanocages/reduced graphene oxide (FeO x @C/rGO) nanocomposites were obtained by calcinating the templates. The optimized Fe2 O3 @C/rGO–2 nanocomposite possesses considerable specific surface area and pore volume, with ultrasmall Fe2 O3 particles (<5 nm) stably embedded in the carbon nanocages. The unique microstructure of the Fe2 O3 @C/rGO–2 electrode results in improved ion/electron accessibility that ensures an admirable specific capacity (713 C g −1  at 1 A g −1 ) and rate capability (67.3% retention at 50 A g −1 ). Meanwhile, the impressive cycling stability (104% retention after 20000 cycles) originates from the dual protection of Fe2 O3 particles by the carbon nanocages and rGO. Furthermore, a hybrid supercapacitor constructed from a Fe2 O3 @C/rGO–2 anode and a nickel foam-supported NiCo2 O4 nanoneedles (NiCo2 O4 –NF) cathode exhibited a maximum energy density of 101.9 Wh kg −1, suggesting that the delicately designed anode material is a promising candidate for constructing advanced energy storage devices. Graphical abstract: Image 1 Highlights: A series of FeO x @C/rGO anode materials are fabricated using P–Fe- MOF/GO templates. The optimized Fe2 O3 @C/rGO–2 anode exhibits a specific capacity of 713 C g −1  at 1 A g −1 and 67.3% retention at 50 A g −1 . The capacity retention of the Fe2 O3 @C/rGO–2 anode is 104% after 20000 cycles at 20 A g −1 . The hybrid supercapacitor is constructed using the Fe2 O3 @C/rGO–2 anode and NiCo2 O4 –NF cathode. The hybrid supercapacitor delivers an energy density of 101.9 Wh kg −1  at a power density of 800 W kg −1 .